Optimalisasi Penanganan Emesis Gravidarum pada Kehamilan Trimester I melalui Edukasi dan Terapi Nonfarmakologis di Dusun Ceret, Desa Mantang, Kec. Batukliang - Fatmah, Siti; Ningsih, Nining Fatria; Wahyuni, Ervin Dini (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Emesis gravidarum is a common condition in first-trimester pregnant women, characterized by nausea and vomiting due to hormonal changes, such as increased levels of estrogen and HCG. This condition can affect maternal and fetal health, potentially leading to dehydration, electrolyte imbalances, and even preterm birth. This study aims to optimize the management of emesis gravidarum through education and non-pharmacological therapy in Dusun Ceret, Desa Mantang, Kecamatan Batukliang, Lombok Tengah. The research employs a descriptive quantitative approach with purposive sampling, involving 20 first-trimester pregnant women. Interventions include small-group education sessions and non-pharmacological therapies such as relaxation techniques, acupressure, and dietary modifications. Data were collected through questionnaires and observations and analyzed descriptively and inferentially. The results showed an increase in participants' understanding from 60% to 80% and a reduction in the intensity of emesis gravidarum symptoms. This intervention proved effective in improving the quality of life for pregnant women and can serve as a guideline for healthcare providers in delivering community-based services. In conclusion, educational and non-pharmacological therapy approaches can effectively assist pregnant women in managing emesis gravidarum, supporting maternal and fetal health.